A 60-year-old man with isaacs mertens-syndrome a rare entity (Bangladesh Journal of Medical Science, 2021)
Isaacs-mertens syndrome also known as neuromyotonia is a rare neuromuscular disorder caused by hyperexcitability and continuous firing of axons of the nerve that innervate the muscle fibers. It is an immune-mediated disorder with elevated antibody level against voltage gated potassium channels (VGKC). Symptoms include progressive muscle weakness, continuously twitching muscles (myokymia), cramping, increased sweating and delayed muscle relaxation. This is a case report of a 60-year-old man who presented with pain and weakness of right lower limb for 3 months, which gradually became worse to involve both the lower and upper limbs. NCS revealed to have motor neuropathy and EMG showed fibrillations and fasciculations with positive sharp waves. After which he was diagnosed with Isaacs-mertens syndrome and was followed up for 8 weeks with medications and physiotherapy management.Bangladesh Journal of Medical Science Vol.20(3) 2021 p.691-693